الحماية الدستورية( كيف نحمي الدستور وكيف يحمينا) (Comprehensive Journal of Science, 2026)
This study examines the constitutional protection of public rights and freedoms as a fundamental pillar of the rule of law. It emphasizes that merely enshrining rights in the constitution is insufficient to guarantee their effectiveness; rather, they must be supported by the principle of constitutional supremacy and effective judicial review of constitutionality. The research discusses the constitutional value of rights and freedoms and analyzes the impact of exceptional circumstances, particularly states of emergency, on their exercise and guarantees. It affirms that the principle of legality remains applicable even in extraordinary conditions, provided that emergency measures are subject to judicial oversight. The study concludes that constitutional judiciary represents the true safeguard for protecting rights and freedoms by annulling unconstitutional laws and maintaining a balance between state authority and individual rights.
Keywords: Constitutional supremacy, rights and freedoms, judicial review, rule of law, state of emergency, principle of legality